Dutch desease scare in Kazakhstan: is it real? - Balázs Égert; Carol S. Leonard (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
In this paper we explore the evidence that would establish that Dutch disease is at work in, or poses a threat to, the Kazakh economy.Assessing the mechanism by which fluctuations in the price of oil can damage non-oil manufacturing-and thus long-term growth prospects in an economy that relies heavily on oil production-we find that non-oil manufacturing has so far been spared the perverse effects of oil price increases from 1996 to 2005.The real exchange rate in the open sector has appreciated over the last couple of years, largely due to the appreciation of the nominal exchange rate.We analyze to what extent this appreciation is linked to movements in oil prices and oil revenues.Econometric evidence from the monetary model of the exchange rate and a variety of real exchange rate models show that the rise in the price of oil and in oil revenues might be linked to an appreciation of the U.S. dollar exchange rate of the oil and non-oil sectors.But appreciation is mainly limited to the real effective exchange rate for oil sector and is statistically insignificant for non-oil manufacturing.
URN:NBN:fi:bof-201408071996
Keywords: E43; E50; E52; C22; G21; O52; 330; price level; inflation; Balassa-Samuelson; tradables; house prices; regulated prices; Europe; transition